The two‐way relationship between ionospheric outflow and the ring current. Issue 6 (3rd June 2015) - Welling, D. T.; Jordanova, V. K.; Glocer, A.; Toth, G.; Liemohn, M. W.; Weimer, D. R.
Abstract: It is now well established that the ionosphere, because it acts as a significant source of plasma, plays a critical role in ring current dynamics. However, because the ring current deposits energy into the ionosphere, the inverse may also be true: the ring current can play a critical role in the dynamics of ionospheric outflow. This study uses a set of coupled, first‐principles‐based numerical models to test the dependence of ionospheric outflow on ring current‐driven region 2 field‐aligned currents (FACs). A moderate magnetospheric storm event is modeled with the Space Weather Modeling Framework using a global MHD code (Block Adaptive Tree Solar wind Roe‐type Upwind Scheme, BATS‐R‐US), a polar wind model (Polar Wind Outflow Model), and a bounce‐averaged kinetic ring current model (ring current atmosphere interaction model with self‐consistent magnetic field, RAM‐SCB). Initially, each code is two‐way coupled to all others except for RAM‐SCB, which receives inputs from the other models but is not allowed to feed back pressure into the MHD model. The simulation is repeated with pressure coupling activated, which drives strong pressure gradients and region 2 FACs in BATS‐R‐US. It is found that the region 2 FACs increase heavy ion outflow by up to 6 times over the noncoupled results. The additional outflow further energizes the ring current, establishing an ionosphere‐magnetosphere mass feedback loop. This study further demonstrates that ionospheric outflow is not merely a plasma source for the magnetosphere but an integral part in the nonlinear ionosphere‐magnetosphere‐ring current system. Key Points: Region 2 field‐aligned currents drive additional ionospheric O + outflow This additional outflow feeds the ring current, creating a feedback system Ionospheric outflow is a tightly coupled piece of the M‐I system